2008
DOI: 10.1002/rcm.3833
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multi‐mycotoxin liquid chromatography/tandem mass spectrometry method for sweet pepper analysis

Abstract: A multi-mycotoxin method was developed for the simultaneous determination of trichothecenes (nivalenol, deoxynivalenol, 3-acetyldeoxynivalenol, 15-acetyldeoxynivalenol, neosolaniol, fusarenon-X, diacetoxyscirpenol, HT-2 toxin, T-2 toxin), aflatoxins (aflatoxin-B(1), aflatoxin-B(2), aflatoxin-G(1) and aflatoxin-G(2)), Alternaria toxins (alternariol, alternariol methyl ether and altenuene), fumonisins (fumonisin-B(1), fumonisin-B(2) and fumonisin-B(3)), ochratoxin A, zearalenone, beauvericin and sterigmatocystin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 22 publications
0
81
0
1
Order By: Relevance
“…For this reason there was the need to perform SPE clean-up using SAX SPE cartridges with the aim of obtaining a satisfactory recovery for this analyte. Data from the literature revealed that prior to SAX SPE clean-up, complete ionization of FB 1 was achieved when the pH of the sample extract (in this case, sweet pepper extract) was adjusted to between 5.8 to 6 [44]. However, in this study, complete ionization of FB 1 was achieved at pH 6.5-7, which highlights once more the influence of sample matrix on the ionization of FB 1 [45].…”
Section: Comparison Of Sax Spe and Oasis Hlb Spe Clean-up Approachesmentioning
confidence: 54%
“…For this reason there was the need to perform SPE clean-up using SAX SPE cartridges with the aim of obtaining a satisfactory recovery for this analyte. Data from the literature revealed that prior to SAX SPE clean-up, complete ionization of FB 1 was achieved when the pH of the sample extract (in this case, sweet pepper extract) was adjusted to between 5.8 to 6 [44]. However, in this study, complete ionization of FB 1 was achieved at pH 6.5-7, which highlights once more the influence of sample matrix on the ionization of FB 1 [45].…”
Section: Comparison Of Sax Spe and Oasis Hlb Spe Clean-up Approachesmentioning
confidence: 54%
“…The combination of LLE with SPE is applied for carrots (Solfrizzo et al, 2004), food supplements (Diana di Mavungu et al, 2009), sweet peppers (Monbaliu et al, 2009), cereal, fruit and vegetable products (Asam et al, 2010) and irradiated soya beans ). Nawaz et al (1997 combined LLE with gel permeation chromatography (GPC) for the detection of Alternaria toxins in oilseed rape meal and sunflower seed meal.…”
Section: Sample Preparationmentioning
confidence: 99%
“…LC-MS/MS appears to be most promising as a highly specific, broadly applicable detection method that provides both qualitative and quantitative data. Considering the possible contamination of foodstuffs by several mycotoxin producing fungal species and the production of different types of mycotoxins by one mould, a trend is to develop methods suitable for the determination of several mycotoxins in a single run (Sewram et al 1999;Monti et al 2000;Rundberget and Wilkins 2002;Royer et al 2004;Berthiller et al 2005;Cavalière et al 2005;Kokkonen et al 2005;Sorensen and Elbaek 2005;Abbas et al 2006;Delmulle et al 2006;Monbaliu et al;Sulyok et al 2006;Spanjer et al 2008). Currently published protocols, however, have been developed and optimized for different foods and feeds.…”
Section: Introductionmentioning
confidence: 99%